2019
DOI: 10.1111/nph.15706
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic consequences of interploidal hybridisation in synthetic and natural interspecific potato hybrids

Abstract: Summary Interploidal hybridisation can generate changes in plant chromosome numbers, which might exert effects additional to the expected due to genome merger per se (that is genetic, epigenetic and phenotypic novelties). Wild potatoes are suitable to address this question in an evolutionary context. To this end, we performed genetic (AFLP and single sequence repeart (SSR)), epigenetic (MSAP), and cytological comparisons in: (1) natural populations of the diploid cytotype of the hybrid taxonomic species Sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…The effect of the initial graft is traumatic to the plant (Melnyk, 2017) and elicits a multitude of genome-regulatory responses, but it also requires long-term management of molecular communication between different genomes, similar to what occurs in interspecifichybrids. This result is concordant with previous research in different systems that has shown that genome-genome interactions result in an epigenomic signature, for example, in interspecific hybrids (Gaut et al, 2007;Landry et al, 2007;Ishikawa and Kinoshita, 2009;Wu et al, 2013;Cara et al, 2019) and in allopolyploids (Springer et al, 2015). One implication of the graftassociated epigenomic variation reported here is that specific scion genotypes could be epigenomically predictable based on the rootstock to which they are grafted.…”
Section: The Chambourcin Methylome Bears a Signature Of Graftingsupporting
confidence: 93%
“…The effect of the initial graft is traumatic to the plant (Melnyk, 2017) and elicits a multitude of genome-regulatory responses, but it also requires long-term management of molecular communication between different genomes, similar to what occurs in interspecifichybrids. This result is concordant with previous research in different systems that has shown that genome-genome interactions result in an epigenomic signature, for example, in interspecific hybrids (Gaut et al, 2007;Landry et al, 2007;Ishikawa and Kinoshita, 2009;Wu et al, 2013;Cara et al, 2019) and in allopolyploids (Springer et al, 2015). One implication of the graftassociated epigenomic variation reported here is that specific scion genotypes could be epigenomically predictable based on the rootstock to which they are grafted.…”
Section: The Chambourcin Methylome Bears a Signature Of Graftingsupporting
confidence: 93%
“…However, they observed in the allopolyploids considerable but regional re‐patterning in the DNA methylation landscape that was missing in the diploid hybrid genomes, indicating that in this system hybridity can exacerbate, only in combination with polyploidy, a rewiring of epigenetic and gene expression landscape. The instability in the DNA methylation landscape is even greater in the case of interploidal hybrids as shown in a study of several natural and artificial cytotypes of Solanum (Cara et al , 2019).…”
Section: Epigenetic Relevance Of Hybridization and Whole Genome Doublingmentioning
confidence: 96%
“…This work was supported by Agencia Nacional de Promoción Científica y Tecnológica and Universidad Nacional de Cuyo, Argentina PICT 1243. This protocol was adapted from our previous work (Cara et al, 2019).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Wild potatoes (Solanum, section Petota) are a group of species related to the cultivated potato Solanum tuberosum L. Internal breeding barriers can be incomplete, thus, interspecific hybridization occurs in areas of sympatry (Camadro et al, 2012). Epigenetic changes in response to interspecific hybridization have been documented in synthetic and natural hybrids of wild potato species (Cara et al, 2019). Solanum x rechei H. & H. is a hybrid species that grows in sympatry with its wild progenitors, Solanum kurtzianum B.…”
mentioning
confidence: 99%